Ali Abd Al-Raziq and the Political Movement of the Caliphate System - Yusuf, Maulana (Research and Development Institution, Darussalam Institute for Islamic Studies, 2020)
This essay attempts to elaborate on the phenomenon of the political movement of the caliphate system according to Ali Abd Al-Raziq. Using critical analysis, this essay concludes that Al-Raziq essentially rejects the caliphate system. According to Al-Raziq, Muslims need to form a state based on reason alone which is influenced by situations and conditions, not based on religion. Therefore, there is no single system in an Islamic state, let alone having a normative justification. Al-Raziq also views that government affairs are worldly matters, not religious matters. He seeks to separate religious affairs from political affairs.